Effect of Laser Acupuncture and Auricular Acupressure in a Child with Trismus as a Sequela of Medulloblastoma. Issue 2 (April 2014) - Ferreira, Danielly Cunha Araújo; De Rossi, Andiara; Torres, Carolina Paes; Galo, Rodrigo; Paula-Silva, Francisco Wanderley Garcia; de Queiroz, Alexandra Mussolino
In several countries the most common cause of death in young people is cancer. Patients with head and neck cancer often have complications after cancer treatment. Radiation therapy can cause oral trismus, which is related to high doses of radiation. Although acupuncture is reported to be effective and is widely used for the treatment of peripheral facial paralysis by promoting an improvement of motor functions, few reports in the literature demonstrate its effectiveness. We report a case in which the symptoms of a patient with facial paralysis after surgical cancer treatment associated with chemotherapy and radiotherapy improved after laser treatment at acupuncture points. Ten weekly sessions of laser therapy were conducted, using the Twin laser device, applied to systemic acupuncture points (LR3, LI4, LI18, LI19, LI20, SI17, SI19, ST4, ST6, ST7, GV20), together with 10 weekly sessions of auricular acupressure. Significant improvement of the trismus was seen, confirmed by the increase in mouth opening from 33.26 to 53.3 mm. The patient's family also noted reduced anxiety and hyperactivity. These results suggest that laser acupuncture and auricular acupressure for trismus and facial paralysis following cancer treatment is worth further investigation.